Inflammation mediates the association between the Prognosis Nutrition Index (PNI) and mortality in acute pancreatitis: evidence from international cohorts - Huang, Lingwei; Xiao, Dan; Yan, Lingjie; Liao, Juan; Yang, Meimei; He, Fei (Frontiers in Immunology, 2026)
BackgroundThe prognostic nutritional index (PNI), reflecting nutritional and immune-inflammatory status, has been linked to outcomes across a range of disorders. Its prognostic value in acute pancreatitis (AP) and the potential mediating role of systemic inflammatory response syndrome (SIRS) remain unclear.ObjectiveTo investigate whether systemic inflammatory response syndrome (SIRS) mediates the linkage between the prognostic nutritional index (PNI) and risk of death from any cause during hospitalization, as well as short- and long-term outcomes, in patients with acute pancreatitis (AP).MethodsThis was an international retrospective cohort study utilizing the U.S. MIMIC-IV dataset (v2.2) and a hospital-based dataset in China, encompassing 2,574 patients diagnosed with AP (MIMIC cohort: 941; Chinese cohort: 1,633). Analyses included multivariable Cox regression, receiver operating characteristic (ROC) curves, Kaplan–Meier survival curves, restricted cubic spline (RCS) modeling, subgroup analysis, and mediation analysis.ResultsAfter adjustment for age, sex, comorbidities, and BISAP scores, PNI remained to serve as a standalone protective factor among AP patients (all HR < 1, P < 0.05). PNI exhibited strong predictive performance, particularly for long-term mortality. The low PNI exhibited markedly greater mortality compared with those with high PNI at all time points (log-rank P < 0.01). PNI demonstrated a significant nonlinear negative correlation with mortality, with more pronounced protective effects in certain subgroups. SIRS partially mediated the PNI–mortality association.ConclusionPNI is an independent determinant of mortality in AP, offering complementary prognostic value to BISAP. SIRS partially mediates this association but is not the primary pathway.